Influence of Oxygen Vacancy Density on the Polaronic Configuration in Rutile - Liu, Rulin (Materials (Basel), 2018)
Polaronic configurations that were introduced by oxygen vacancy in rutile TiO(2) crystal have been studied by the DFT + U method. It is found that the building block of TiO(6) will expand when extra electron is trapped in the central Ti atom as polaron. With manually adjusting the initial geometry of oxygen vacancy structure, a variety of polaronic configurations are obtained after variable-cell relaxation. By calculating different sizes of supercell model, it is found that the most stable configuration can be influenced by the density of oxygen vacancy. With increasing interaction between vacancies, the most stable polaronic configuration change from small polaronic configuration to mixed configuration.